The impact of Eastman's aniline plant explosion on process safety awareness. Issue 1 (6th August 2015) - Lodal, Peter N.
Abstract : A single presentation covering one person's first‐hand experience with a significant process safety incident, delivered at the beginning of OSHA's PSM regulation still provides contemporary lessons, even though the actual incident occurred more than 50 years ago. Lessons include: (a) stopping operations unilaterally or getting expert help when readings are unexpected or unusual, (b) establishment of a testing regimen that covers a broad range of conditions, especially those that can be achieved under abnormal circumstances (e.g., fire), and (c) the impact of "restore to original condition" maintenance activities that otherwise might not be analyzed if treated as a replacement‐in‐kind only. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 103–106, 2016